Spatial distribution of brachyuran crabs in Sarawak with emphasis on fiddler crabs (Genus UCA) as biomonitors of heavy metal pollution - Huet, Charmaine Andrea (Universiti Malaysia Sarawak (UNIMAS), 2000)
This study consisted of intertidal surveys to determine the general distribution and zonation of intertidal Brachyuran crabs along the coast of Sarawak and investigations into the use of fiddler crabs (genus Uca) as a biological monitor for heavy metal pollution. The suitability of fiddler crabs as biological monitors was examined by correlating the concentrations of eight heavy metal in the sediment and in the crab tissues, to the population density of the crabs. It was hypothesized that high concentrations of heavy metals would result in low population densities. Population density was estimated by counting the number of open burrows during low tide, assuming a 1:1 burrow-occupancy ratio after preliminary trials. Sediment samples and crab specimens were analysed for heavy metals using atomic absorption spectrometry. The sediment was also examined for particle size, pH and Eh, and percentage of organic matter.